Habitação Social: circunstâncias para o ofício do arquitecto. O Bairro da Pasteleira - Joana Isabel Milhais Mendonça Ferreira (2016)
The purpose of this work is to know Pasteleira's housing estate as a social housing project and to understand how space is crucial in people's lives.The research on the origin of the housing estate and on the context in which it was built shows the constraints Pasteleira's housing estate was subjected to, being one of the first housing estates built under the "Plano de Melhoramentos da cidade do Porto" (1956/1966).Using reports and testimonies of inhabitants of the housing estate, this work analyses the evolution of the two housing types therein and of its relationship with its surroundings, trying to understand how gradual change in social habits, technological innovation and urban development influence changes in architecture.Intervention hypotheses, of greater or lesser extent, try to answer to the main identified problems, restructuring and redefining the spaces of the residential building, on the assumption that 'every house is a case' and hence the need for flexible, adaptable and versatile solutions.Knowing that in housing at controlled costs the architect is dependent on circumstances that will affect his work, this dissertation searches for an answer to the question: how can architecture meet the needs and desires of people in social and economically disadvantaged contexts?